Atheroprotective Immunity and Interleukin-10 Linked to Reduced Characteristics of Plaque Stability - Yu, Yinda; Lin, Shiying; Pan, Yueyun; He, Ning; Wu, Yanzhao; Ahmed, Osman; Hedin, Ulf; Karlsson, Mikael C.I.; Li, Nailin; Gisterå, Anton (JACC-BASIC TO TRANSLATIONAL SCIENCE, 2025)
[Display omitted] •Ongoing development of immunotherapies for cardiovascular disease aims to boost atheroprotective responses.•Studying the long-term implications of atheroprotective immunity in mice revealed 2 distinct pathways.•The IL-10 pathway was associated with characteristics of reduced plaque stability and increased recurrent cardiovascular events in humans.•Further research should explore ways to enhance atheroprotective pathways without compromising plaque stability. Autoimmunity to low-density lipoprotein (LDL) is linked to atherosclerosis, with LDL immunization proposed as a preventive measure, but the mechanisms of atheroprotective immunity are not well understood. We investigated T-cell responses to LDL using 2 T-cell receptor transgenic mouse strains. At 52 weeks, BT1×HuBL mice showed reduced atherosclerosis, increased humoral responses against LDL, and lower plasma cholesterol. Conversely, BT3×HuBL mice had reduced atherosclerosis without changes in cholesterol, linked to increased type 1 regulatory T cells, interleukin (IL)-10 production, and decreased characteristics of plaque stability. In human plaques, IL10 mRNA negatively correlated with collagen content, and IL-10 inhibited collagen production in vitro. We conclude that atheroprotective LDL immunity elicits 2 distinct pathways: lipid-lowering immune responses and local anti-inflammatory IL-10 production. Because IL-10 is associated with decreased plaque stability and increased risk of cardiovascular events, treatments aimed at promoting IL-10 signaling over extended periods to reduce vascular inflammation should be carefully monitored.